On purposefulness of application of physical culture-health related technology for prophylaxis of students’ respiratory system disorders - V.L. Kondakov; E.N. Kopeikina; A.N. Usatov (Physical Education of Students, 2016)
Purpose: To give scientific foundation and experimental proof of physical culture-health related technology for prophylaxis of respiratory system disorders. Material: in the research students: girls (n= 43) and boys (n=40) participated. In process of academic physical culture classes students practices: dozed health walks )as warming up), respiratory exercises by methodic of A.N. Strelnikova and G. Childers (which were used as main corrective mean of respiratory system’s functional state), health swimming (for motor functioning intensification) outdoor games (as mean of active leisure). Results: The conducted research witness about general positive influence of the worked out technology of disorders’ prophylaxis on students’ somatic health. The technology was constructed on the base of synthesis of the most effective means of health related physical culture. In its basis we put generalized data about their impact. Main characteristic of this technology is its orientation on definite health improvement tasks in compliance with peculiarities of trainees’ contingent. The technology permits to present its content and orientation as integral mean of strengthening of organism’s functional potentials as well as ensuring of high effectiveness of students’ educational process. It permits to significantly reduce impacts of respiratory system’s disorders. Conclusions: The worked out technology permits to present its content and orientation as integral mean of strengthening of organism’s functional potentials.